Efficacy of Medical Treatment for Infantile Hypertrophic Pyloric Stenosis: A Meta-analysis - Shu-Fen Wu; Hsiang-Yu Lin; Fu-Kuei Huang; An-Chyi Chen; Bai-Horng Su; Chia-Ing Li; Hung-Chih Lin (Pediatrics and Neonatology)
Infantile hypertrophic pyloric stenosis (IHPS) is a common disease in infancy. Pyloromyotomy is universally considered the treatment for IHPS; however, oral or intravenous atropine has been reappraised for the treatment of IHPS in the past 20 years. We investigated the efficacy of atropine in the medical management of IHPS by using meta-analysis and investigated the sonographic changes of the pyloric canal, as well as the efficacy and adverse effects of atropine. Methods: Information was retrieved from PubMed, Ovid, and MEDLINE. The efficacy and adverse effects of atropine treatment for IHPS were reviewed using the standard process of meta-analysis. Results: Eleven articles were obtained. Five reports showed that 77 of 110 (70%) infants who were administered oral atropine benefitted by the induced remission of IHPS. Six reports showed that 288 of 345 (83.5%) patients who were treated initially with intravenous atropine then changed to oral atropine showed beneficial effects and had no serious side effects. Time to pyloric muscle normalization ranged from 5 weeks to 15 months. Conclusion: The study results indicate that atropine is a possible alternative treatment for IHPS, particularly in infants with major concurrent disease, and is safe without obvious side effects.